(3TQM GdTGajIs - (3Qcf GdOjf CHh eMeO GdMSf Hf eMeO GdGSJQGHGOis; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s ((3GHQGgje Hf GdMGL YhV Hf LHjdg Hf MSf GdMfai s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi JhGdi fYeg hfhGdg abO EdJeS efi LeGYI Cf CTQM GdebOeI ai GdJUQja GdefShHg Edi LeGd GdOjf CHj YeQh YKeGf TQMkG Sgd bhdg GdJUQja Yde HCUhd JYQa HgG CMhGd CHfjI Gdcde s
(3BNQgG (B:s
(3hCeG cJGHI Hdi HGdjGA adbhg EeGdJgG hESJZdGd GdCeGdI ai GdOdGdI Ydi GdjGA ZGdHkG hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
Keywords: (3GdfMhs